Coreografias didáticas e transmidiáticas em feiras escolares inovadoras - Carvalho, Alex Medeiros de (2018)
In this qualitative research of participant type, developed in the research line "Education in Sciences and Mathematics" of the Graduate Program in Brazilian Education from the Federal University of Uberlândia (UFU), we analyzed the trajectory of a student group on their experiences with the Internet of Things (IoT). For this group, IoT was the paradigm in building applications (apps) to control remotely, using some mobile device (tablet) with Android Operating System (OS), of four existing experiments - apps presented at the school fair in which they were studying. The research question was: how to make school fair a didactic choreography of technological innovation and convergence of media in basic education? The research took place at the Federal Institute of Education, Science and Technology of Triângulo Mineiro (IFTM). When determining the subjects of the research, my role as a professional investigator was established, having the role of the interested audience, considered "researcher", the student collective and the professor advisor, all of the school chosen as the scenario. We used participant observation and the constructions of recorded video reports, semi-structured interviews and blogs and discussion forums established in groups on social networks. We gave up on triangulation and interpretation of meanings, aiming to describe, analyze and interpret the collective trajectory of knowledge building in Science and Mathematics of this research team. Finally, we present the thesis that the Convergence Culture can make school fairs a didactic choreography of technological innovation and media convergence in basic education since the necessary conditions for this choreography are established and that the scenario is organized in order to enable learning.